1989
DOI: 10.1080/00102208908924048
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition of Single Droplets of Two-Component Liquid Fuels

Abstract: Measurements and predictions of the ignition delay time of single droplets of several twocomponent mixtures at atmospheric pressure are presented. The results show that ignition is controlled by the more volatile component o r the mixture. The ignition delay time is found to be nearly independent of species transport in the liquid phase. Mixture reaction rates are shown to be adequately modelled by simple linear combination of component rate data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In the first configuration, a fiber-suspended droplet is exposed to a hot, stagnant environment in a preheated furnace, and the ignition delay time is measured, based on an appropriate ignition criterion, by using an optical technique. This approach has been used by Nishiwaki [35], El-Wakil and Abdou [36], Faeth and Olson [25], Kadota et al [37], Saitoh et al [26], Bergeron and Hallett [38,39], Tanabe et al [40,41], Marchese et al [42,43], and many others. The second configuration involves a freely falling droplet in a furnace or a droplet injected into a heated stream.…”
Section: Experimental Studies On Droplet Ignitionmentioning
confidence: 99%
“…In the first configuration, a fiber-suspended droplet is exposed to a hot, stagnant environment in a preheated furnace, and the ignition delay time is measured, based on an appropriate ignition criterion, by using an optical technique. This approach has been used by Nishiwaki [35], El-Wakil and Abdou [36], Faeth and Olson [25], Kadota et al [37], Saitoh et al [26], Bergeron and Hallett [38,39], Tanabe et al [40,41], Marchese et al [42,43], and many others. The second configuration involves a freely falling droplet in a furnace or a droplet injected into a heated stream.…”
Section: Experimental Studies On Droplet Ignitionmentioning
confidence: 99%
“…By developing a model, Bergeron et al [48] showed that the ignition of binary droplets is controlled by the more volatile component. Experiments and numerical analysis have also suggested that increasing the concentration of more volatile component can significantly reduce the ignition delay [49,50].…”
Section: Droplet Ignitionmentioning
confidence: 99%
“…Since the fundamental mechanisms such as vaporization and chemical reactions greatly depend on fuel composition, it is important to study on the spontaneous-ignition behaviors of alkane/ethanol binary-fuel droplets. Some of the previous studies treated the spontaneous ignition of binary-fuel droplets [5][6][7][8] . However, most of them studied hydrocarbon/hydrocarbon fuels, and the study on hydrocarbon/alcohol fuel is very limited 8) .…”
Section: Introductionmentioning
confidence: 99%